Novel Pyrimidine Derivatives: Microwave-Assisted Synthesis and Computational Insights Toward Anti-Inflammatory Activity - Gaware, Vinayak Madhukar; Dhamak, Kiran Bhausaheb; Kunde, Vikas Damu; Gaikar, Mayur Trimbak (International Journal of Pharmaceutical Investigation, 2026)
Aim/Background: This study focuses on the synthesis and evaluation of novel pyrimidine derivatives as potential anti-inflammatory agents. Materials and Methods: The compounds were synthesized via a two-step process: condensation of acetophenone with aromatic aldehydes yielded substituted chalcones, which were then cyclized with guanidine hydrochloride using Microwave-Assisted Organic Synthesis (MAOS). This green chemistry method afforded high yields (70-90%) in short reaction times (10-15 min). The synthesized derivatives were characterized using FT-IR, ¹H-NMR, TLC, elemental analysis, and melting point determination. PASS prediction and molecular docking indicated promising anti-inflammatory potential via inhibition of Taurine dehydrogenase. Results: In vivo evaluation using the Carrageenan-Induced Rat Paw Edema model, with Nimesulide as reference, confirmed significant anti-inflammatory activity in several compounds. Conclusion: These findings demonstrate a correlation between structural features and biological activity. The integration of green synthesis, in silico modeling and pharmacological testing supports the development of pyrimidine derivatives as promising anti-inflammatory candidates.
Keywords: Pyrimidine derivatives; Anti-inflammatory activity; Microwave-assisted synthesis; Molecular docking; PASS prediction.